Biochromic silole derivatives: a single dye for differentiation, quantitation and imaging of live/dead cells. Issue 5 (10th August 2018) - Chen, Sijie; Liu, Jianzhao; Zhang, Shouxiang; Zhao, Engui; Yu, Chris Yee Yung; Hushiarian, Roozbeh; Hong, Yuning; Tang, Ben Zhong
Abstract : A new method using a single cell-permeable biochromic fluorescent dye to differentiate, quantify and image both live and dead cells is reported. Abstract : Differentiating between live and dead cells is a critical step for biological researchers, clinical doctors and pharmaceutical engineers when evaluating cell viability, for determining compound cytotoxicity and in the development of effective treatments for many diseases. Usually, careful selection and combination of two different dyes are required to differentiate and image both live and dead cells. In this work, we present a new method that can differentiate, quantify and image both live and dead cells concurrently through the use of a single, cell-permeable, biochromic fluorescent dye. Two silole-based hemicyanine dyes, Silo-Cy and Silo-2Cy are designed and synthesized. These dyes exhibit green fluorescence in both live and dead cells but much stronger green and red fluorescence only from dead cells. By collecting signals from the two distinct channels, we are able to image and discriminate between live and dead cells through fluorescence microscopy and quantify the cell viability via flow cytometry.